A novel method to purify small RNAs from human tissues for methylation analysis by LC-MS/MS - Yang, Rong; Li, Jianfeng; Wu, Yifan; Jiang, Xinli; Qu, Shuang; Wang, Qiang; Liang, Hongwei; Zen, Ke (Frontiers in Molecular Biosciences, 2022)
Methylation modification of small RNA, including miRNA, piRNA and tsRNA, is a critical for small RNA biogenesis and biological function. Methylation of individual small RNA can be defined by Liquid Chromatography-Coupled with Mass Spectrometry (LC-MS/MS). However, LS-MS/MS analysis requires high purity of individual small RNA. Due to the difficulty of purifying specific small RNA from tissues or cells, the progress in characterizing small RNA methylation by LC-MS/MS is limited. Here we report a novel method that can efficiently purify small RNA from human tissues for LC-MS/MS analysis. This method includes two steps: 1) To pull down target small RNA by incubating total small RNAs (18-24nt) extracted from human tissue with a biotinylated antisense oligonucleotide of target small RNA with two extra adenosine (A) residues at its 5´-end, followed by capturing biotinylated antisense-small RNA-binding complex via streptavidin magnetic beads, and 2) To protect target small RNA by pairing it with a single-strand DNA, which sequence is complementary to target small RNA, to form a DNA/RNA hybrid double-strand, followed by sequentially digestion with exonuclease I, nuclease S1 and DNase I, respectively. Employing a mixture of 4 pairs of synthetic methylated and non-methylated small RNAs, we further refined this two-step method by optimizing nuclease S1 treatment condition. With this method, we successfully purified miR-21-5p, miR-26-5p, piR-020485 and tsRNA from human lung and sperm tissue samples and analyzed their 2’-O-methylation modification at the 3’-end by LC-MS/MS.